Levantamento populacional de fungos micorrízicos arbusculares e de fitonematoides em áreas produtoras de algodão no estado de Goiás - Ferreira, Bruno da Silva (2015)
Different management strategies are necessary for the control of plant nematodes. The arbuscular mycorrhizal fungi (AMF) have been an option as potential microorganisms for biological control. There is a demand of ways to manage plant parasitic nematode with less environmental impact and lower cost. Thus, the aim of this study was to survey nematodes and AMF in cotton producing areas in the state of Goiás and evaluate the interaction between AMF and nematodes, and relate their populations to the physical and chemical soil traits. The survey was conducted during two crop seasons (June/2013 and February/2014) in ten cotton producing areas. Three samples composed of ten subsamples were collected in each area. Soil and roots were collected in the depth of 0 to 20 cm. For quantification and identification of AMF and nematodes soil and root analysis were carried out in the laboratory. There was also the analysis of physical and chemical soil properties. For data analysis we used the Pearson correlation coefficient, principal component analysis (PCA) and the diversity indexes of Shannon-Wiener, Simpson and Margalef. In all sampled areas was observed occurrence of nematodes, the main genera being Meloidogyne, Pratylenchus, Helicotylenchus, Rotylenchus, Rotylenchulus, Aphelenchus and Criconemoide. The Helicotylenchus and Pratylenchus genres presented higher abundance in the two years of study, followed by Meloidogyne. The major cause of cotton damage, Rotylenchulus sp. was not observed in 80% of the sampled areas, with presence only in two areas in the first crop season (2013). Different AMF species were found, being the main genre Glomus, with most species. AMF were distributed evenly among the evaluated areas and in the two crop seasons. The correlation between Aphelenchus species and AMF Cetraspora pellucida was positive, as well as between Meloidogyne and Glomus sp. On the contrary, the correlation between G. macrocarpum and Pratylenchus was negative. The largest quantity of organic matter negatively affected Helicotylenchus sp. and positively the AMF R. intraradices. The higher phosphorus content influenced positively the population of Glomus sp. Areas cultivated with cotton in the state of Goiás with greater presence of AMF have a lower number of nematodes in the soil and roots.